Diagnostic Yield of Bronchial Biopsy Versus Bronchial Washing in Endoscopically Visible Lung Cancer in Tishreen University Hospital - صبيح, لينا; محمد الخير,; رنا عيسى , (Latakia University Journal -Medical Sciences Series, 2023)
Globally, lung cancer is the second most commonly diagnosed cancer, and it is also the leading cause of cancer-related death. In 2020, Although the incidence of the disease continuous to claim in the older ager. Various environmental and host factor may also affect the risk of lung cancer, but tobacco use is the single most important risk factor for cancer. No method has proven more valuable than endoscopic examination of the tracheobronchial tree. Bronchial washing, brushing and forceps biopsies are often combined to increase the diagnostic yield. Objective of the study: To compare the diagnostic yield of bronchial washing and bronchial biopsy in endoscopically visible lung cancer. In a prospective cohort study on (128) patients with clinical and radiological suspicion of lung cancer at Tishreen University Hospital, Lattakia, Syria, during the period between 2021-2022. Patients underwent flexible bronchoscopy, bronchial washing and then bronchial biopsies were taken from those who had visible lesions by bronchoscopy, so the last number of patients who completed the all three procedures were 94 patients. The Results showed: from 94 patients with endoscopically visible lung cancer, lung cancer was confirmed in 75 patients by either bronchial biopsy, bronchial washing or both of them. The average age of the patients was 61.95 years. The number of males was 76 (80%), and females 18 (20%). Male: female ratio was 4.2:1. The number of smokers was 89 (94.7%) of the study sample, and (83.1%) of them were males. The most common tissue type was squamous cell carcinoma (29.17%) and small cell carcinoma (29.17%), followed by adenocarcinoma (22.22%), then non-small cell carcinoma (18.06%) and large cells carcinoma (1.39%). The diagnostic yield of bronchial biopsy was (76.59%) and the diagnostic yield of bronchial washing was (46.81%). The diagnostic yield was higher when we combine both procedures to be (79.78%). The best results that we can get are when a bronchial washing is combined with a bronchial biopsy in endoscopically visible lung cancer.